Elevating Industry IQ: The Dance of Empowerment, Resourcefulness, and Innovation in Petrochemical Realms - Akhtar, Nadeem (International Review of Management and Marketing, 2024)
Aim of research was to explore the connections between perceived organizational support, job resourcefulness, and innovation. Our investigation also investigated into the mediating role played by job psychological empowerment in these relationships. Data was collected from 25 petrochemical companies, amassing 100 valuable datasets. These were analyzed using PLS-SEM 4. Findings cast light on important role that employee empowerment plays as a mediator in the link between job resourcefulness and innovation. Job resourcefulness indeed wields a significant total impact on innovation, this effect dissipates when the lens shifts to include empowerment. This underscores the pivotal importance of empowerment in the complex relationship between job resourcefulness and innovation. The study advances our understanding of the intricate dynamics of perceived organizational support, job resourcefulness, psychological empowerment, and innovation within the petrochemical industry. Notably, it introduces the concept of job psychological empowerment as a mediator between resourcefulness and innovation, adding depth to existing models.